Severe urinary tract damage secondary to primary bladder neck obstruction in women. - Pedro F S Freitas; Augusto Q Coelho; Homero Bruschini; Eric S Rovner; Cristiano M Gomes (PLoS ONE)
Objective To present the clinical and radiological characteristics of women with severe structural deterioration of the bladder and upper urinary tract secondary to Primary Bladder Neck Obstruction (PBNO), and their outcomes after bladder neck incision (BNI). Methods Retrospective evaluation of adult women who underwent BNI for PBNO at one institution. Patients were assessed for symptoms, renal function, structural abnormalities of the urinary tract and video-urodynamics. PBNO diagnosis was confirmed with video-urodynamics in all patients. BNI was performed at the 4-5 and/or 7-8 o'clock positions. Postoperative symptoms, PVR, uroflowmetry and renal function were evaluated and compared to baseline. Results Median patient age was 56.5 years (range 40-80). All presented with urinary retention-four were on clean intermittent Catheterization (CIC) and two with a Foley catheter. All patients had bladder wall thickening and diverticula. Four women had elevated creatinine levels, bilateral hydronephrosis was present in five (83.3%). After BNI, all patients resumed spontaneous voiding without the need for CIC. Median Qmax significantly improved from 2.0 [1.0-4.0] mL/s to 15 [10-22.7] mL/s (p = 0.031). Median PVR decreased from 150 to 46 [22-76] mL (p = 0.031). There were no postoperative complications. Creatinine levels returned to normal in 3/4 (75%) patients. Conclusion PBNO in women may result in severe damage to the bladder and upper urinary tract. Despite severe structural abnormalities of the bladder, BNI was effective in reducing symptoms and improving structural and functional abnormalities of the lower and upper urinary tract.